The forever strong playbook : a six-week, science-based plan to sharpen your mind, strengthen your body, and get healthy at any age - Lyon, Gabrielle (Osteopath) (Atria Books, 2026)
"Get fit, prevent disease, and future-proof your body with step-by-step strategies to build strength, reduce fatigue, and sharpen your focus at any age."--Publisher description.